Comparing Smartphone, WhatsApp, Facebook, Instagram, and Snapchat: Which Platform Elicits the Greatest Use Disorder Symptoms? - Rozgonjuk, Dmitri; Sindermann, Cornelia; Elhai, Jon D; Montag, Christian (Cyberpsychology, behavior and social networking, 2021)
In recent years, smartphone and social networking services (SNS) use have received a great amount of scholarly attention regarding their potentially addictive effects. Conceptualized as smartphone or SNS use disorder, research has consistently demonstrated relations with daily-life impairments. However, Smartphone Use Disorder (SmUD), WhatsApp Use Disorder (WAUD), Facebook Use Disorder (FBUD), Instagram Use Disorder (IGUD), or Snapchat Use Disorder (SCUD) scores have not been compared with each other. This comparison could provide insight into which device/platform could be most related to daily-life impairments. The effective sample of this study comprised 439 German-speaking individuals (age = 25.08, = 9.74; 271 women) who reported actively using a smartphone, as well as WhatsApp, Facebook, Instagram, and Snapchat, and responded to the respective use disorder scales. Within-subjects analysis of variance and tests ( values adjusted with the Holm method) were used to compare smartphone and SNS use disorder scale scores. The results suggest that SmUD scores are highest in comparison with other SNS platforms. Although WAUD and IGUD scores did not differ from each other, these scores were higher than for FBUD and SCUD. SCUD scores were higher than FBUD scores. These results provide novel insight into how the smartphone and different SNSs may relate to engagement in problematic digital technology use.